The capabilities and human rights of high performance athletes - Adams, A.; Kavanagh, E. (International Review for the Sociology of Sport, 2020)
High performance athletes participate and function in sports systems where exploitative behaviours may become manifest. These behaviours potentially violate an individual athlete`s human rights. Using the Capability Approach first outlined by Amartya Sen the paper details how a more precise analysis of human rights, in the context of high performance sport, may be achieved. Using in-depth narrative accounts from high performance athletes, data illustrate how athlete maltreatment is related to individual capabilities and functionings: the loss of individual freedoms infringes accepted notions of human rights. The implications for practice concern how human rights may be protected within and for systems of high performance production.